Advances in the Application of Black Phosphorus-Based Composite Biomedical Materials in the Field of Tissue Engineering - Wanying Qi; Ru Zhang; Zaishang Wang; Haitao Du; Yiwu Zhao; Bin Shi; Yi Wang; Xin Wang; Ping Wang (MDPI AG, 2024)
Black Phosphorus (BP) is a new semiconductor material with excellent biocompatibility, degradability, and optical and electrophysical properties. A growing number of studies show that BP has high potential applications in the biomedical field. This article aims to systematically review the research progress of BP composite medical materials in the field of tissue engineering, mining BP in bone regeneration, skin repair, nerve repair, inflammation, treatment methods, and the application mechanism. Furthermore, the paper discusses the shortcomings and future recommendations related to the development of BP. These shortcomings include stability, photothermal conversion capacity, preparation process, and other related issues. However, despite these challenges, the utilization of BP-based medical materials holds immense promise in revolutionizing the field of tissue repair.